THU0328 Predictors of severe damage in anca-associated vasculitis: data from a monocentric inception cohort. (15th June 2017) - Felicetti, M; Padoan, R; Cerchiaro, M; Zen, M; Punzi, L; Schiavon, F
Abstract : Background: Granulomatosis with polyangiitis (GPA) and microscopic polyangiitis (MPA) are multi-systemic diseases associated with anti-neutrophil cytoplasmic antibodies (ANCA). Patients develop severe and irreversible damage, even in early stages of the disease, but data about prognostic factors are limited. Objectives: To assess items and predictors of severe damage in a monocentric cohort of ANCA-associated vasculitis (AAV) patients, classified as GPA or MPA. Methods: Clinical and serological data of patients, followed-up in a daily practice setting, were retrospectively revised. Severe damage, defined as a Vasculitis Damage Index (VDI) 3 5, was assessed after 12 months and at last examination (LE). The five most important items, predictors of severe damage and their increase rate were analysed at the beginning and at the last examination. Results: 69 patients were included, 53 (76.8%) classified as GPA and 16 (23.2%) as MPA. According to EUVAS classification 7 (10.1%) were affected by limited disease, 14 (20.3%) by early systemic disease, 35 (50.7%) by generalized disease and 13 (18.9%) by severe disease. Patients were middle aged at diagnosis (54.6±15 years) with a diagnostic latency of 9.6±16.4 months, mostly caucasian (98.6%) and equally represented in sex (female 53.6%). Mean follow-up was 54.5±41.9 months. The number of flare/year at LE was significantly higher in anti-PR3 patients if compared to anti-MPO (1.0±1.1 vs 0.3±0.5, p=0.028). The VDI items most frequently observed are listed in Figure 1 . We measured their frequencies and increase rate from diagnosis to the LE: arterial hypertension increased from 3 (4.7%) to 41 (65.1%) (+60.3% (IC 95% 48–71%), p<0.0001), GFR<50% from 1 patient (1.6%) to 28 (44.4%) (+42.8 (IC 95: 31–55), p<0.0001), neuropathy from 4 (6.3%) to 22 (34.9%) (+28.6% (IC 18–41), p<0.0001), diabetes from 0 (0%) to 11 (17.5%) (+17.5% (IC 10–29); p=0.0011) and proteinuria>0.5 g 24 h from 1 (1.6%) to 13 (20.6%) (+19% (IC 11–31); p=0.0006). Severe damage, defined as VDI≥5, increased over time, being present in none patient at diagnosis and in 14 (25.9%) at last examination. At univariate analysis, number of flares/year (p=0.012), BVASv3 at diagnosis (p=0.03), steroid pulses therapy (p=0.04) and steroid cumulative dose (p=0.03) were identified as predictive factors of severe damage in the first year. Conversely, creatinine at LE (p=0.04), numbers of hospitalizations (p=0.009) and steroid cumulative dose at LE (p=0.47) were found to be predictors of long-term severe damage. Interestingly, ANCA pattern did not influence damage severity and only slightly differences in VDI items was noted between anti-PR3 and anti-MPO positive patients. Conclusions: Our results highlights that knowing severe damage predictors is key in short and long term treat to target patient's management. Disclosure of Interest: None declared